Docetaxel suppresses immunotherapy efficacy of natural killer cells toward castration‐resistant prostate cancer cells via altering androgen receptor‐lectin‐like transcript 1 signals. Issue 10 (25th May 2020) - Tang, Min; Gao, Shenglin; Zhang, Lei; Liu, Bianjiang; Li, Jie; Wang, Zengjun; Zhang, Wei
Abstract: Background: Docetaxel is an effective first‐line chemotherapy agent used in the treatment of castration‐resistant prostate cancer (CRPC) patients. However, most times chemotherapy with docetaxel eventually fails due to the development of docetaxel resistance. Natural killer (NK) cells are the first line of defense against cancer and infections. NK cell function is determined by a delicate balance between signals received via activating and inhibitory receptors. The aim of this study is to explore whether the potential docetaxel‐resistant mechanism is associated with impaired NK cell cytotoxicity toward CRPC cells. Methods: By performing MTT assay, we explored the role of docetaxel in regulating NK cells' cytotoxicity. Western blot and quantitative real‐time polymerase chain reaction analysis were used to measure messenger RNA and protein levels separately. Luciferase reporter assay and chromatin immunoprecipitation assay were performed to analyze the mechanism. Results: We found that docetaxel could suppress the immunotherapy efficacy of NK cells toward CRPC cells via the androgen receptor (AR)‐lectin‐like transcript 1 (LLT1) signals in vitro. Analysis of the mechanism revealed that docetaxel functioned through increasing AR to upregulate LLT1 expression in CRPC cells. AR transcriptionally activated LLT1 expression by binding to its promoter region. Furthermore, targeting AR with ASC‐J9 or blocking LL1 by anti‐human LLT1 monoclonal antibody could reverse the suppressive effect of docetaxel on the immunotherapy efficacy of NK cells toward CRPC cells. Conclusions: We concluded that chemotherapy agent docetaxel could increase AR that transcriptionally regulated the expression of NK inhibitory ligand LLT1 on CRPC cells. An increase of LL1 may further suppress the immunological efficacy of NK cells to kill CRPC cells. Additionally, targeting AR or blocking LL1 could enhance the immunotherapy efficacy of NK cells toward CRPC cells which might be considered as a new therapeutic option for the prevention or treatment of docetaxel resistance.